The Effect of Exchange Rates, India’s GDP, and Global Price Fluctuations on Indonesia’s CPO Exports to India - Benius; Rambu Anarki; Puput Iswandyah Raysharie (Institut Bisnis dan Informatika Kesatuan, 2025)
Indonesia’s crude palm oil plays a vital role in global vegetable oil markets, with India consistently ranking as one of its main importers amid dynamic macroeconomic conditions. This study examines how exchange rates, India’s GDP, and international CPO prices affect Indonesia’s crude palm oil exports to India from 1994–2024. Using a quantitative approach with time-series data, secondary sources were obtained from the Central Bureau of Statistics, UN Comtrade, and the World Bank. Classical assumption tests and multiple linear regression were performed using Stata. The results show that the IDR exchange rate has a positive and significant effect on crude palm oil export volumes, indicating that depreciation improves export competitiveness. In contrast, India’s GDP has a negative and significant effect, suggesting that economic growth is associated with import diversification and substitution toward domestic vegetable oils. International CPO prices exhibit a positive but insignificant effect, reflecting relatively inelastic demand in India’s food industry. The F-test confirms that all variables jointly influence exports, with the model explaining 66.44% of export variation. The study highlights the crucial role of exchange rates and the paradoxical impact of India’s economic growth, implying that Indonesia should diversify markets, strengthen trade negotiations, and improve production efficiency.